Réponses

2014-09-11T15:25:18+02:00
A = 27*101
A = 27*(100+1)
A = 27*100+27*1
A = 2700+27
A = 2727

B = 99*57
B = 57*(100-1)
B = 57*100+57*(-1)
B = 5700-57
B = 5643

C = 1002*53
C = 53*(1000+2)
C = 53*1000+53*2
C = 53000+106
C = 53106

D = 998*24
D = 24*(1000-2)
D = 24*1000+24*(-2)
D = 24000-48
B = 23952
2014-09-11T15:49:02+02:00

Bonjour


A = 27 x 101
A = 27 x (100 + 1)
A = 27 x
100 + 27 x 1
A = 2700 + 27
A = 2 727

B = 99 x 57
B = 57 x (100 - 1)
B = 57 x 100 + 57 x -1
B = 5700 - 57
B = 5 643

C = 1002 x 53
C = 53 x (1000 + 2)
C = 53 x 1000 + 53 x 2
C = 53 000 +106
C = 53 106

D = 998 x 24
D = 24 x (1000-2)
D = 24 x 1000 + 24 x (-2 )
D = 24 000 - 48
D = 23 952